Students Transitioning to College and Out of Competitive Sport: Athletic Identity, Coping, and Stress - Alex Michael Russell; Michael Cottingham; Adam Barry; Don Lee; David Walsh (Journal of Applied Sports Management, 2018)
High-school athletes who transition into higher education as non-athlete students encounter several social and emotional difficulties. The purpose of this study is to investigate the influences of aforementioned participants’ athletic identities on their utilization of coping strategies and resulting perceptions of stress. A structural model was developed and empirically tested using a 48-item questionnaire. The sample population consisted of undergraduate students enrolled in freshman-level courses at three public southwestern universities. Structural equation modeling (SEM) indicated a strong model fit, including a significant correlation between various factors of athletic identity and coping, as well as a significant correlation between coping and stress. Assessing the athletic identities of competitive athletes at all levels could serve to identify those who may be susceptible to difficulties upon transitioning out of competitive sport and prone to a reliance on ineffective coping efforts. Subscribe to JASM
Keywords: athletic identity; coping; stress; college